Chromium (Cr) Content In Water, Gills, and Muscles of Tilapia Fish (Oreochromis niloticus) in Tukad Badung, Bali - Alfani Sebayang; Alfi Hermawati Waskita Sari; Gde Raka Angga Kartika (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2026)
Increased human activity along the Tukad Badung River affects the quality of the river's water. One of the causes is waste from various anthropogenic activities containing heavy metals, which can affect the quality of water and the organisms living in it. The purpose of this study was to determine the chromium (Cr) content in water and tilapia (Oreochromis niloticus). The study was conducted in the Tukad Badung River from February to March 2023. The sampling technique used the time-composite and sample-composite methods. The results of the study showed that the Tukad Badung waters were not polluted, as the Cr content did not exceed the thresholds set by Government Regulation of the Republic of Indonesia No. 82 of 2001 and Bali Governor Regulation No. 8 of 2007. Meanwhile, the Cr content in the muscles of tilapia at station II was 0.036 mg/L, and at station III, it was 0.727 mg/L in the muscles and 2,220 mg/L in the gills. The highest Bioconcentration Factor (BCF), which was found in the gills of tilapia, was 74, but the level of Cr accumulation ability at all stations in the Tukad Badung waters was still classified as a low accumulative category.